Ответы и объяснения

2013-04-12T18:26:48+00:00

6а+3b=3(2a+b)

a=100-b

Подставляем: 3(200-2b+b)=3(200-b)=600-3b

600-3b=639

3b=600-639=-39

b=-13

Проверим: a=113, b=-13

6*113-3*13=678-39=639

Значит 6а+3b=639 при a=113 и b=-13 => числа целые, ответ:может

2013-04-12T18:29:06+00:00

a+b=100

6a+3b=639

 

a=100-b

6a+3b=639

 

a=100-b

6(100-b)+3b=639

 

a=100-b

600-6b+3b=639

 

a=100-b

3b=-39

 

a=100-b

b=-13

 

a=100-(-13)

b=-13

 

a=113

b=-13

 

Проверяем

113+(-13)=100

6*113+3*(-13)=678+(-39)=639